Signal detection algorithm for cognitive radio using singular value decomposition - Omar, Mohd Hasbullah; Hassan, Suhaidi; Amphawan, Angela; Awang Nor, Shahrudin (2011)
This paper highlights an algorithm for detecting the presence of wireless signal using the Singular Value Decomposition (SVD) technique.We simulated the algorithm to detect common digital signals in wireless communication to test the performance of the signal detector.The SVD-based signal detector was found to be more efficient in detecting a signal without knowing the properties of the transmitted signal.The performance of the algorithm is better compared to the favorable energy detection.The algorithm is suitable for blind spectrum sensing where the properties of the signal to be detected are unknown.This is also the advantage of the algorithm since any signal would interfere and subsequently affect the quality of service (QoS) of the IEEE 802.22 connection.Furthermore, the algorithm performed better in the low signalto-noise ratio (SNR) environment.